Information Design and the COVID-19 pandemic: What is the contribution to health and citizenship? - Guimaraes, Cayley; Filho, Marco A. Mazzarotto; Weslley de Souza Bastos, José (International Journal for Innovation Education and Research, 2022)
Multiple and various graphic design pieces were created around the world for digital media during the COVID-19 pandemic. These graphic design pieces were meant to disseminate information about the disease caused by the new Corona Virus SARS-CoV-2 to inform people on how to better protect themselves. Information Design uses guidelines and principles that would inform the design of useful graphic pieces to combat the pandemic and help the people to address their health needs for citizenship rights. This research analyzed multiple pieces made available by Fiocruz (a Brazilian health institution). The case study presented in this paper explores the piece with information explaining how soap acts on the virus and proposes a new design to improve its quality.